The Humoral Immune Response to BCG Vaccination - Tanner, Rachel; Villarreal-Ramos, Bernardo; Vordermeier, H. Martin; McShane, Helen (Frontiers in Immunology, 2019)
Bacillus Calmette Guérin (BCG) is the only currently available vaccine against tuberculosis (TB), but it confers incomplete and variable protection against pulmonary TB in humans and bovine TB (bTB) in cattle. Insights into the immune response induced by BCG offer an underexploited opportunity to gain knowledge that may inform the design of a more efficacious vaccine, which is urgently needed to control these major global epidemics. Humoral immunity in TB and bTB has been neglected, but recent studies supporting a role for antibodies in protection against TB has driven a growing interest in determining their relevance to vaccine development. In this manuscript we review what is known about the humoral immune response to BCG vaccination and re-vaccination across species, including evidence for the induction of specific B cells and antibodies; and how these may relate to protection from TB or bTB. We discuss potential explanations for often conflicting findings and consider how factors such as BCG strain, manufacturing methodology and route of administration influence the humoral response. As novel vaccination strategies include BCG prime-boost regimens, the literature regarding off-target immunomodulatory effects of BCG vaccination on non-specific humoral immunity is also reviewed. Overall, reported outcomes to date are inconsistent, but indicate that humoral responses are heterogeneous and may play different roles in different species, populations or individual hosts. Further study is warranted to determine whether a new TB vaccine could benefit from the targeting of humoral as well as cell-mediated immunity.